Unmet needs of the Iranian mothers of the children with cancer and the identification of the related factors: A descriptive-correlational study - Khanali Mojen, Leila; Rassouli, Maryam; Ashrafizadeh, Hadis; Fathollah Zadeh, Ensieh; Dadashi, Nasrin; Khoubbin Khoshnazar, Tahereh Alsadat; Pourazarhagh, Parand; Nasrabadi, Tahereh (Frontiers in Psychology, 2022)
Abstract Introduction: Parents’ caring responsibilities lead to imbalances in roles, functions, and emotions, confronting them with new needs that, if left unaddressed, have adverse consequences for the lives of all family members. Therefore, this study aimed to identify the significant unmet needs of the mothers of the children with cancer. Method: This descriptive cross-sectional study was conducted in Tehran in 2019-2020 on 215 mothers of the children with cancer visiting the hospitals affiliated with medical universities. The study population was selected through convenience sampling method and according to the inclusion criteria. The FIN questionnaire consisting of two subscales, FIN-Import and FIN-Fulfillment, with 40 items, was used to collect data. Results: The mean age of the mothers participating in the study was 34.77 ± 7.91 years, and the mean age of the children with cancer was 9.77 ± 14.37 years. The mean scores of FIN-Import and FIN-Fulfillment were 92.88 ± 7.97 and 70.82 ± 17.89, respectively. The phrase “To know the facts concerning my child’s prognosis” with 23. %, and the phrase “To be told about the people who could help with problems” with 22.8% were the most common unmet needs reported by the parents. Conclusion: The present study indicated that caring for a child with cancer had confronted mothers with new needs to be met; however, not all of these needs had been satisfied. Awareness about the unmet needs of these mothers and planning to manage those needs can lay the groundwork to improve their health.